Lipoblastoma in infant: Our experience - Tommaso Armenise; Ottavio Gentile; Antonio Orofino; Samuele Leggio; Maria Paola Lanzillotto; Francesca Zullino; Guglielmo Paradies (Elsevier, 2015)
Lipoblastoma is a rare benign soft tissue tumor that occurs most commonly in infants and children. The wide majority are detected in children under the age of 3 years. Lipoblastoma usually present as a rapidly growing mass most often located in the trunk and extremities. Lipoblastoma has rarely been reported in the inguino-labial region. No malignant degeneration has been documented while a high recurrence rate has been described and is usually correlated to the diffuse-type lesions (lipoblastomatosis) and to incomplete excision.